Geography's Quantitative Revolutions : Edward A. Ackerman and the Cold War Origins of Big Data - Wyly, Elvin K. (Book collections on Project MUSE., 2019)
"This book traces the recent history of geography, information, and technology through the biography of Edward A. Ackerman, an important but forgotten figure in geography's 'quantitative revolution.' It argues that Ackerman's work helped encode the hidden logics of a distorted philosophical heritage -- a dangerous, cybernetic form of thought known as militant neo-Kantianism -- into the network architectures of today's pervasive worlds of surveillance capitalism"--